Time-resolved x-ray imaging of a laser-induced nanoplasma and its neutral residuals. (13th April 2016) - Flückiger, L; Rupp, D; Adolph, M; Gorkhover, T; Krikunova, M; Müller, M; Oelze, T; Ovcharenko, Y; Sauppe, M; Schorb, S; Bostedt, C; Düsterer, S; et al.
Abstract: The evolution of individual, large gas-phase xenon clusters, turned into a nanoplasma by a high power infrared laser pulse, is tracked from femtoseconds up to nanoseconds after laser excitation via coherent diffractive imaging, using ultra-short soft x-ray free electron laser pulses. A decline of scattering signal at high detection angles with increasing time delay indicates a softening of the cluster surface. Here we demonstrate, for the first time a representative speckle pattern of a new stage of cluster expansion for xenon clusters after a nanosecond irradiation. The analysis of the measured average speckle size and the envelope of the intensity distribution reveals a mean cluster size and length scale of internal density fluctuations. The measured diffraction patterns were reproduced by scattering simulations which assumed that the cluster expands with pronounced internal density fluctuations hundreds of picoseconds after excitation.